Strategic outlook in business and finance innovation : multidimensional policies for emerging economies - Yüksel, Serhat; Dinçer, Hasan, 1982- (Emerald Publishing Limited, 2021)
Financial markets have developed rapidly since the 1980s, crossing national borders, and a new financial order has emerged. As a result of increasing competition in this new market, financial institutions and companies have had to improve and renew themselves. The emergence of new financial products has become essential. One of the recent trends observed in financial markets is in financial innovation, with the purpose of ensuring markets are efficient and competitive, along with increasing profitability and reducing risk. Strategic Outlook in Business and Finance Innovation: Multidimensional Policies for Emerging Economies, edited by Hasan Dinçer and Serhat Yüksel, brings together new theoretical frameworks and develops appropriate strategies to improve the performance of firms globally. Vital issues are examined, including customer retention policies, generating new products based on customer needs, clarifying organizational goals, active participation of all organization for idea generation, analysing industry trends and benchmarking in competitive market environments. In this collection, global perspectives are offered with contributions and examples from Asia, Eastern Europe, Latin America and Africa, as well as other emerging economies, which give illuminating insights for scholars of business, management and finance.